Analisa Bentuk Lagu dan Makna Lagu Uli Karya Bram Tobing - Dedek Darma Adi Purba; Ance Juliet Panggabean (Journal on Education, 2022)
This research is an analysis of the form and description of the meaning of the song Uli by Bram Tobing. This study used qualitative research methods. The development of popular music in Indonesia is due to the influence of technology and rapidly growing electronics. It is easy and cheap to produce music and record music using the audio Midi (Musical Instrument Digital Interface) application, the many digital music platforms and social media networks to publish musical works, have made popular regional music very developed at this time. Bram Tobing is one of the musicians who carry out the process of creating, recording and publishing independently (Indie) without involving sponsorship or collaboration from any music label. Uli's song is one of the songs that was created, recorded using an application, Midi audio, and published through digital platforms and social networking media. The result in analyzing Uli's song using Prier's theory is a 3-part song form consisting of A (a and a'), B (b and b') and C (c and z). Then there are intros, verses I and II, transitions, choruses, interludes and song repetitions. In describing meaning, the writer uses theory using Ferdinand De Saussure's theory. The meaning contained in the song Uli is about the first sight of a man who falls in love with a woman and has the desire to build a relationship together, both in joy and sorrow.